Blood markers of cardiac stress after generalized convulsive seizures. (15th January 2019) - Nass, Robert D.; Motloch, Lukas J.; Paar, Vera; Lichtenauer, Michael; Baumann, Jan; Zur, Berndt; Hoppe, Uta C.; Holdenrieder, Stefan; Elger, Christian E.; Surges, Rainer
Summary: Objective: Generalized convulsive seizures (GCS) are associated with high demands on the cardiovascular system, thereby facilitating cardiac complications. To investigate occurrence, influencing factors, and extent of cardiac stress or injury, the alterations and time course of the latest generation of cardiac blood markers were investigated after documented GCS. Methods: Adult patients with refractory epilepsy who underwent video–electroencephalography (EEG) monitoring along with simultaneous one‐lead electrocardiography (ECG) recordings were included. Cardiac biomarkers (cardiac troponin I [cTNI]; high‐sensitive troponin T [hsTNT]; N‐terminal prohormone of brain natriuretic peptide [NT‐proBNP]; copeptin; suppression of tumorigenicity‐2 [SST‐2]; growth differentiation factor 15, [GDF‐15]; soluble urokinase plasminogen activator receptor [suPAR]; and heart‐type fatty acid binding protein [HFABP]) and catecholamines were measured at inclusion and at different time points after GCS. Periictal cardiac properties were assessed by analyzing heart rate (HR), HR variability (HRV), and corrected QT intervals(QTc). Results: Thirty‐six GCS (6 generalized‐onset tonic–clonic seizures and 30 focal to bilateral tonic–clonic seizures) were recorded in 30 patients without a history of cardiac or renal disease. Postictal catecholamine levels were elevated more than twofold. A concomitant increase in HR and QTc, as well as a decrease in HRV, was observed. Elevations of cTNI and hsTNT were found in 3 of 30 patients (10%) and 6 of 23 patients (26%), respectively, which were associated with higher dopamine levels. Copeptin was increased considerably after most GCS, whereas SST‐2, HFABP, and GDF‐15 displayed only subtle variations, and suPAR was unaltered in the postictal period. Cardiac symptoms did not occur in any patient. Significance: The use of more sensitive biomarkers such as hsTNT suggests that signs of cardiac stress occur in about 25% of the patients with GCS without apparent clinical symptoms. SuPAR may indicate clinically relevant troponin elevations. Copeptin could help to diagnose GCS, but specificity needs to be tested.